Bioinspired Bottlebrush Polymers Effectively Alleviate Frictional Damage Both In Vitro and In Vivo - Pham, Duy Anh (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.